1909 Me. Laws 257 - (:unkn) unknown (My University, 1909)
Ch. 206, § 113-Military Parades by Unauthorized Bodies Prohibited: No body of men, other than the active militia and the troops of the United States, shall associate themselves together as a military company or organization, or parade in public with firearms in any city or town of this state; nor shall any city or town raise or appropriate any money toward arming, equipping, uniforming or in any other way supporting, sustaining or providing drill rooms or armories for any such body of men;
Keywords: MILITIAS